(untitled) (Global Journal of Management and Business Research, 2016)
The paper studies the inter-relationship between advertisement expenditure, sales and profit. Taking ten-year data (2005-06 to 2014-15) of twenty manufacturing companies indexed in NSE’s NIFTY, the study applied various models including descriptive study, correlation and regression. The tools used (Regression and Correlation) clearly show that there is a significant relationship between advertisement expenditure, sales and profit. The study concludes that there is a one-sided relationship between advertisements, sales and profit wherein advertisement expenditure positively impacts the sales and profit of the business in case of Indian manufacturing companies.